IMPACT OF CELEBRITY ENDORSER (SELEBGRAM) ON CONSUMER PURCHASE INTEREST IN THE ONLINE HIJAB FASHION INDUSTRY: Case Study on Muslim Women Who Follow Celebrities On Instagram In Social Media - Mei Supriyani; Titus Indrajaya; Sri Yulianti; Qotrunnada Qotrunnada (International Journal of Economy, Education and Entrepreneurship, 2022)
Now the form of hijab is starting to develop in the past, which was only a cloth veil used to cover the head to the neck. The hijab model is now beginning to be adapted to the fashion trending on Instagram social media. The types of hijab models that are increasingly diverse in patterns, models, and accessories are an attraction for Muslim women. Wearing the hijab is not just to meet fashion needs but as an effort to communicate the values and identity of Muslim women. The purpose of this research is to explain the externalization, objectification, and internalization of online hijab fashion industry people in business, to be able to look stylish on Instagram and the hijaber community program that is fashionable but still fulfills religion. Data gathering approaches included observation, interviews, and questionnaires, which follow a qualitative descriptive method approach. And text analysis of several Selebgram Instagram accounts on the social media of Muslim women who follow. This study uses the theory of Kotler and Keller; Kim; Shimp; Kertamukti; Cahyani; especially the style of dress, the pattern of fashion models is used as an industrial business with the theory of marketing strategies for online hijab products. Products that consumers are interested in models. Celebrity endorsers on Instagram. The results of this study have an impact on consumers who wear hijab with self-awareness as Muslim women and on the surrounding environment. There is a shared understanding of the Celebrity endorser community, the committee covering aurat as an obligation, fashionable hijab as part of da'wah, and modern and flexible Muslim identity. Finally, Community Celebrity endorsers in obedience to religion